An Analysis of the Application of Agroecological Principles: Uma análise da aplicação dos princípios agroecológicos na província de Azuay - Alava Atiencie, Gabriela (2020)
Agroecology is an alternative for social transformation that guarantees the sustainability of life in a world that periodically faces food crisis. There is a lack of information regarding the applicability of agroecological principles by part of organizations carrying out sustainable agriculture as part of the so called Popular and Solidary Economy in Azuay-Ecuador. For this reason, this study aims to analyze the meaningful differences found in the application of agroecological principles by these organizations considering their antiquity, number of members, and municipal division within the province of Azuay. This research used a quantitative approach that made use of the Multifactorial Questionnaire on Sustainability of Agroecological Organizations (MQAO), which was applied to a representative sample of leaders belonging to the organizations. The study shows that most of the organizations do not practice agroecological principles fully. Additionally, it demonstrates that older organizations apply agroecological principles in a larger scale than younger ones; the number of members does not influence principles applicability; it can also be noticed that performance changes from municipality to municipality, being Pucara and Gualaceo the municipalities with the best performance within the province.